Graduate Student Literature Review: Effects of human chorionic gonadotropin on follicular and luteal dynamics and fertility in cattle - T.O. Cunha; J.P.N. Martins (Journal of Dairy Science, 2022)
ABSTRACT: Circulating progesterone concentrations during the growth of the ovulatory follicle and early embryo development have been positively associated with embryo quality and survival and pregnancy success. As a potent luteotropic agent with LH-like activity, human chorionic gonadotropin (hCG) has been tested in different studies to improve pregnancy outcomes by increasing circulating progesterone concentrations during the growth of the ovulatory follicle or early embryonic development. Nevertheless, hCG has produced inconsistent, contradictory, and intriguing results. Furthermore, recent research indicates that hCG, when used before artificial insemination, may affect physiological events necessary for the ovulation of a viable oocyte. In addition, the use of hCG-inducing accessory corpus luteum during the estrous cycle seems to disturb luteolysis and follicle and luteal dynamics during the estrous cycle. This literature review discusses past and current research exploring the effects of hCG on the estrous cycle characteristics and pregnancy per artificial insemination and embryo transfer.